2000
DOI: 10.1177/00220345000790031601
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Xylitol Consumption on Acquisition of Mutans Streptococci by Infants

Abstract: Xylitol is effective as a non-cariogenic sugar substitute. Habitual xylitol consumption appears to select for mutans streptococci (MS) with impaired adhesion properties, i.e., they shed easily to saliva from plaque. One hundred sixty-nine mother-child pairs participated in a two-year study exploring whether the mothers' xylitol consumption could be used to prevent mother-child transmission of mutans streptococci. All mothers showed high salivary levels of mutans streptococci during pregnancy. The mothers in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
4
24

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 34 publications
5
110
4
24
Order By: Relevance
“…2 The 106 mothers randomly allocated to the first study group chewed xylitol gum at least two to three times a day, starting three months after the birth of their child. There were two other study groups: in one, thirty mothers received chlorhexidine varnish six, twelve and eighteen months after delivery; in the other, fluoride varnish was used at the same intervals.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The 106 mothers randomly allocated to the first study group chewed xylitol gum at least two to three times a day, starting three months after the birth of their child. There were two other study groups: in one, thirty mothers received chlorhexidine varnish six, twelve and eighteen months after delivery; in the other, fluoride varnish was used at the same intervals.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 99%
“…2,4 Other evidence has shown that xylitol leads to a reduction in the quantity of plaque, possibly by interfering with mechanisms of adhesion between plaque organisms and the tooth's surface. [65][66][67][68] This is the most likely explanation for the reduced colonisation of mutans streptococci in the mouths of these children.…”
Section: Specific Caries-preventive Actions Of Xylitolmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, comprehensive Finnish "Turku Sugar Study" (Scheinin et al 1976) revealed an 85% decline in dental caries by total dietary substitution of sucrose with xylitol over a 2-year period. Xylitol also has been shown to reduce the vertical transmission of Streptococcus Mutans from mothers to children (Söderling et al 2000). Consequently, promotion of the use of xylitol-sweetened gum has been proposed as a caries-preventive measure in public health (Burt 2006, Honkala et al 1996, Virtanen et al 1996, Isokangas et al 1989.…”
Section: Non-cariogenic Sweetenersmentioning
confidence: 99%
“…[5]Also studies have revealed a reduction in the caries activity in children whose mothers used xylitol products [6,7] as xylitol significantly reduces the levels of mutans streptococci by disrupting the energy production processes leading to a futile energy consumption cycle and cell death. [6][7][8] Preterm infants and infants with very low birth weight experience a higher incidence of enamel (tooth) defects and enamel hypoplasia [9]. Periodontal disease has been linked to preterm labour [10].…”
Section: Introductionmentioning
confidence: 99%